The ubiquitin-like modifier FAT10 does not affect IL-12 expression and signaling - Jinjing Cao; Gerardo Omar Alvarez Salinas; Gunter Schmidtke; Michael Basler (PLoS ONE, 2025)
The ubiquitin-like modifier FAT10 is strongly expressed in dendritic cells (DCs) and upregulated during inflammation. Interleukin (IL)-12 plays a critical role in promoting CD4+ T cell differentiation into Th1 cells and in IFN-γ induction in T cells. Previously, it was shown that FAT10 is required for IFN-γ expression of activated T cells. In this study, we investigated whether FAT10 influences IL-12 expression or IL-12 induced signaling and thereby contributes to the reduced IFN-γ expression. Presence or absence of FAT10 did not alter IL-12 expression in DC2.4 cells and in bone marrow derived DCs. Furthermore, FAT10 had no influence on the differentiation of naïve T helper cells to Th1 cells under Th1 polarizing conditions. Additionally, FAT10 did not alter STAT4 phosphorylation in IL-12 receptor stimulated T cells. Taken together, FAT10 neither influences IL-12 expression in DCs nor affects IL-12 receptor signaling in T cells. Hence, the previously observed influence of FAT10 on IFN-γ secretion is not mediated by IL-12.